Hope, Self Regulated Learning, dengan Problem Focus Coping Mahasiswa Tingkat Akhir - Aquarisnawati, Puri; Patrika, Fauziah Julike (Universitas Trunojoyo Madura, 2024)
Penulisan Skripsi is a subject for student to complete their studies at Bachelor’s level. During the thesis work, students should actively search for theories and literature in various valid sources, read and understanding literature, and also carry out discussions and guidance with the lecturer as their supervisors, but the facts found are that students have behaviors that leads to problem focused coping. The aim of this research is to determine the relationship between hope, self regulated learning, and problem focused coping in final year students. The research method is a quantitative method and uses a saturated sampling as a technique for selecting research subjects. Research data is analized using product moment correlation and multiple correlation techniques to analized minor and major hypotheses. The research result showed that an R value of 0.648 was obtained. Sig value F.Change is 0.000, which shows that 0.000 smaller than 0.05, which means self regulated learning and hope noth have a relationship with problem focused coping. The significance test was to determine the calculated F, obtained as F Change and calculated F smaller than Ftable which was obtained 27.193 more than 3.119. This shows that the major hypothesis is accepted and there is a positive relationship between self regulated learning, hope, and problem focused coping.